Between past and future eight exercises in political thought - Arendt, Hannah (New York Penguin Books, 2006)
Hannah Arendt?s insightful observations of the modern world, based on a profound knowledge of the past, constitute an impassioned contribution to political philosophy. In Between Past and Future Arendt describes the perplexing crises modern society faces as a result of the loss of meaning of the traditional key words of politics: justice, reason, responsibility, virtue, and glory. Through a series of eight exercises, she shows how we can redistill the vital essence of these concepts and use them to regain a frame of reference for the future. To participate in these exercises is to associate, in action, with one of the most original and fruitful minds of the twentieth century.
Includes bibliographical references (p. [275]-294) and index.
Keywords: Civilization, Modern--1950-